ETIKA HINDU DALAM PELAKSANAA UPACARA TUMPEK UYE PADA MASYARAKAT HINDU DI BALI - putra, wayan sunampan (Satya Widya: Jurnal Studi Agama, 2021)
Abstract The implementation of Hindu religious teachings cannot be separated from three religious frameworks, namely; tattwa, morals, and ceremonies. The three of them are always related in every religious ceremony. One of them is the Tumpek Uye ceremony which is carried out with respect to animals, as well as worshiping Sang Hyang Pasupati or called Sang Hyang Rare Angon. This paper tries to describe the Tumpek Uye ceremony performed by the Hindu community in Bali. This paper uses a qualitative type that describes the object of writing and then examines the values ​​contained in it, and is presented with a qualitative descriptive. The descriptions of the discussion of this paper are; Tumpek Uye ceremony is one of the religious ceremonies that is carried out as a form of respect for living creatures, especially pets whose existence is so supportive of human life. The Tumpek Uye ceremony shows the realization of the teachings of Hindu ethics in which humans view animals as creatures that need moral treatment. Animals are not only objects but also moral subjects.